Emotional Well-being of Future Physicians: A Study on Depression, Anxiety, Stress and Its Correlation with Academic Performance among Medical Students in Northern India" - Singh, Rahul; Pathak, Abhishek; Singh, Manish; Rana, Yogi; Yadav, Vishesh (Nepal Journal of Neuroscience, 2025)
IntroductionMedical education is known for its demanding nature and intense academic pressures, often leading to elevated levels of psychological distress among students. Depression, anxiety, and stress are commonly reported mental health concerns that may adversely impact academic performance. This study aimed to assess the prevalence and severity of these psychological parameters among MBBS students and examine their correlation with academic functioning.MethodsA descriptive cross-sectional study was conducted over 18 months at a tertiary care teaching hospital in Sitapur, Uttar Pradesh. A total of 384 MBBS students from all academic years were enrolled using convenient cluster sampling. Data were collected through a self-administered questionnaire including a semi-structured socio-demographic proforma, the DASS-42 for assessing depression, anxiety, and stress, and the Academic Performance Scale (APS). Diagnoses were clinically validated using ICD-10 criteria. Statistical analysis was performed using SPSS v26, employing chi-square tests and multivariate logistic regression.ResultsThe prevalence of depression, anxiety, and stress among participants was found to be 32.0%, 38.0%, and 45.0%, respectively. Severity analysis revealed that a significant proportion of students experienced moderate to extremely severe symptoms. A statistically significant inverse relationship was observed between the severity of depression, anxiety, and stress and academic performance (p < 0.001 for depression, p = 0.001 for anxiety, and p = 0.003 for stress). Logistic regression identified moderate to severe depression (AOR: 2.63), anxiety (AOR: 2.35), and stress (AOR: 1.92) as independent predictors of poor academic outcomes.ConclusionA substantial proportion of MBBS students suffer from psychological distress, which significantly affects their academic performance. These findings underscore the need for routine mental health screening, accessible counseling services, and structured wellness programs within medical institutions to promote emotional resilience and academic success.